2022
DOI: 10.1126/science.abq5868
|View full text |Cite
|
Sign up to set email alerts
|

Direct identification of the charge state in a single platinum nanoparticle on titanium oxide

Abstract: A goal in the characterization of supported metal catalysts is to achieve particle-by-particle analysis of the charge state strongly correlated with the catalytic activity. Here, we demonstrate the direct identification of the charge state of individual platinum nanoparticles (NPs) supported on titanium dioxide using ultrahigh sensitivity and precision electron holography. Sophisticated phase-shift analysis for the part of the NPs protruding into the vacuum visualized slight potential changes around individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…On the stoichiometry TiO 2 surface, the electrostatic (Hartree) potential ( V H ) could exist at a relatively high level, making the electron transfer from metal to support, but on the reduced TiO 2– x surface, the lower V H could lead to the reverse electron transfer from support to metal. This trend also stands in the case of Pt and is directly observed recently by the ultrahigh sensitivity and precision electron holography . As shown in Figure a, the total Bader charge of the Pt cluster is positive on stoichiometry TiO 2 with the charge values around +0.51|e|, while with the extra electrons donated from the Ov site, like Au, the Pt cluster can also act as the electron reservoir on the reduced TiO 2– x surface.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…On the stoichiometry TiO 2 surface, the electrostatic (Hartree) potential ( V H ) could exist at a relatively high level, making the electron transfer from metal to support, but on the reduced TiO 2– x surface, the lower V H could lead to the reverse electron transfer from support to metal. This trend also stands in the case of Pt and is directly observed recently by the ultrahigh sensitivity and precision electron holography . As shown in Figure a, the total Bader charge of the Pt cluster is positive on stoichiometry TiO 2 with the charge values around +0.51|e|, while with the extra electrons donated from the Ov site, like Au, the Pt cluster can also act as the electron reservoir on the reduced TiO 2– x surface.…”
Section: Resultssupporting
confidence: 80%
“…This trend also stands in the case of Pt and is directly observed recently by the ultrahigh sensitivity and precision electron holography. 82 As shown in Figure 1a, the total Bader charge of the Pt cluster is positive on stoichiometry TiO 2 with the charge values around +0.51|e|, while with the extra electrons donated from the Ov site, like Au, the Pt cluster can also act as the electron reservoir on the reduced TiO 2−x surface. By receiving electrons, it will conspicuously convert into a negative species around −0.41| e|.…”
Section: ■ Methodsmentioning
confidence: 94%
“…Especially, there is little known on the nature of interaction between carbon nanomaterials and the metal particles. Recently, the interactions of metal particles (Au, Pt) and metal oxide (TiO2, CeO2) supports were investigated by electron holography technologies, which revealed that the electrical properties of the metal-oxide interfaces could be largely affected by the interfacial oxidation state and the lattice orientation (19). Further study shows that the charge transfer direction between the metal particles and the oxides support could be reversed through different post-synthesis treatments or controlling the distortion of the metal nanoparticles (20).…”
Section: Main Text Introductionmentioning
confidence: 99%
“…Fig.5B presents the bright field images of the Pt-CNTs model, which contains the structure information of both the MWCNTs and the Pt nanoparticle (with CNTs' Moire and Pt atom columns). And the corresponding fast Fourier transform (FFT) revealed that the particle was oriented with the< 1 � 11 >,< 11 � 1 > and < 002 > direction and the < 1 � 11 > direction directly interplayed with the defective carbon surface (shown in Fig5 B), which is the common crystal plane with high catalytic activity(19,48,49). The corresponding crystal texture information of the Pt nanoparticle was shown in Fig.S12.…”
mentioning
confidence: 99%
“…Plasmonic nanomaterials have attracted considerable attention in the area of photocatalysis due to their capacity to harvest solar energy and potential to solve the global energy crisis . Plasmonic photocatalysts, composed of noble metal nanoparticles and semiconductor heterostructures, exhibit outstanding photocatalytic activity, with advantages including the production of hot carriers (electron–hole pairs) by visible light, higher charge carrier separation efficiency, enhanced electromagnetic fields, as well as a photothermal effect. Although plasmonic photocatalysis has been investigated for a relatively short period, impressive progress has been achieved in both fundamental studies and development of highly efficient nanocatalysts. …”
mentioning
confidence: 99%